2006
DOI: 10.1158/1541-7786.mcr-06-0153
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Matrilysin Expression by Antisense or RNA Interference Decreases Lysophosphatidic Acid–Induced Epithelial Ovarian Cancer Invasion

Abstract: Our previous reports show that matrilysin [matrix metalloproteinase (MMP)-7] is overexpressed in epithelial ovarian cancer (EOC) and recombinant MMP-7 promotes EOC invasion in vitro. In the present study, we further evaluated the correlation of MMP-7 expression to EOC invasiveness and examined its role in lysophosphatidic acid (LPA)-induced invasion. By sense and antisense gene transfection in vitro, we show that overexpression of MMP-7 in all MMP-7 stably transfected DOV13 clones significantly enhanced their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 78 publications
0
9
0
1
Order By: Relevance
“…COX-2 is a known mediator of angiogenesis and tumour cell invasiveness, as it leads to production of inflammatory cytokines, growth factors, angiogenic factors, and MMPs in various tumours, as well as in KSHV infected cells [20], [77], [116][122]. We could also show that, similarly to MAP4K4 knockdown, COX-2 silencing or chemical inhibition significantly reduces the invasiveness of KSHV-infected endothelial cells ( figure 6A, 6C ).…”
Section: Discussionmentioning
confidence: 76%
“…COX-2 is a known mediator of angiogenesis and tumour cell invasiveness, as it leads to production of inflammatory cytokines, growth factors, angiogenic factors, and MMPs in various tumours, as well as in KSHV infected cells [20], [77], [116][122]. We could also show that, similarly to MAP4K4 knockdown, COX-2 silencing or chemical inhibition significantly reduces the invasiveness of KSHV-infected endothelial cells ( figure 6A, 6C ).…”
Section: Discussionmentioning
confidence: 76%
“…In vitro studies show that MMP-7 expression correlated with EOC invasiveness and that lysophosphatidic acid induced EOC invasion through the secretion/activation of MMP-7 [17]. Modification of non-ECM proteins, such as insulin-like growth factor binding proteins, heparin-binding epidermal growth factor precursor and E-cadherin, by MMP-7 is one of the mechanisms by which MMP-7 plays a role in tumorigenesis [reviewed in reference 14].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of tissue MMP-7 was seen in many malignancies such as prostate, stomach, colorectal, lung, esophageal, liver, pancreas, skin, breast, head and neck [reviewed in reference 14]. Previous studies showed that MMP-7 was overexpressed in EOC surgical specimens and ovarian cancer cell lines [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…LPA Stimulated Migration of ID8 and SKOV3 Cells via cPLA 2 -, COX-1-, and 15-LOX-Dependent Pathways Similar to human EOC cells (24,(35)(36)(37)(38)(39)(40), LPA (1 μmol/L) induced migration of ID8 cells toward four different extracellular matrix proteins: collagen I, fibronectin, laminin, and vitronectin ( Supplementary Fig. S1A).…”
Section: Lpa Did Not Stimulate Proliferation In Twodimensional Cell Cmentioning
confidence: 92%